'But I did not do anything!' – analysing the YouTube videos of the American Muslim televangelist Baba Ali: delineating the complexity of a novel genre. Issue 3 (27th May 2018) - El Naggar, Shaimaa
ABSTRACT: Televangelism or preaching religion via TV and YouTube represents an interesting media phenomenon in which religious messages are presented in an entertaining manner. Despite the novelty of televangelism and its popularity, little attention has been paid to the investigation of the features of this genre, which could allow insights into the nature of this phenomenon and the reasons behind its popularity. In this study, I focus on the case study of the American Muslim televangelist Baba Ali who gained popularity through a series of videos on YouTube. With insights from the Discourse Historical Approach and the Framework of Visual Grammar, I analyse four key aspects of Ali's videos i.e. religious invocation, video-edition and self-representation, use of humour and interactivity. I demonstrate that Ali's videos represent a novel genre that embeds features of the sermon, video-blogs and YouTube culture. Furthermore, I show that Baba Ali represents a new type of a religious figure whose authority appears to emanate from his ordinariness as he presents himself as one of his audience; and from his playfulness. Thus, I elaborate on contemporary Muslim televangelism and extend the application of Critical Discourse Studies to religious discourse, a domain little examined from a critical perspective.